Still 500 million to reach - Glasgow, Robert Edward, 1922-1996 (Bath, UK Echoes of Service, 1974)
Includes photographs.
Brethren writer. Donated by the author - signed inscription.
Keywords: Glasgow, Robert Edward, -- 1922-1996; Glasgow, Heather, -- d. 2001; Brethren movement -- Missionaries -- India -- Biography